Automatic Spray Pump of Hand Sanitizer Tool for Helping Aisyiah Clinic GKB - Rini Puji Astutik; Darmawan Aditama; Putri Aisyiyah Rakhma Devi; Yoedo Ageng Suryo; Eko Budi Leksono (OJS Universitas Muhammadiyah Gresik, 2020)
Covid-19 Pandemic is a severe problem for all countries in the entire world, including Indonesia. The government has made much effort by giving raw food to all of society who have lower income or got impact from Pandemic. The other government's actions are Large Scale Social Restriction (PSBB), using masker, washing Hands with soap. To cut the contagion chain that it has not run well this moment. This activity needs more personal protective equipment such as masker and Hand Sanitizer; both tools are essential for tackling patients in the medical sector. In the Pandemic era, these tools are minimal, and also, the price is very high, so their stock tent to the shortage. The Muhammadiyah University of Gresik, as part of the Muhammadiyah Organization, has contributed to the society around the campus. We have done one activity making an automatic spray pump of Hand Sanitizer for helping Aisyiah Clinic as Muhammadiyah Health Facility. A mechanical spray pump of Hand Sanitizer is a tool used to avoid touching the tools; just put the Hand close to the device, and then spray a little bit of Hand sanitizer. Besides, we give an Automatic Spray Pump of Hand Sanitizer; we also offer two jerry cans refilling of hand sanitizer and masker. As per the interview with the doctor who works there, they are very appreciative of this giving, and it is beneficial for this clinic.